Sei sulla pagina 1di 1

The Leibnitz Formula for the n’th Derivative of a Product

Theorem 1. Let u(x) and v(x) be functions of class C n , i.e. functions with continuous n’th derivative. Then their product is also of class C n , and

where

d

n

dx n [u(x)v(x)] =

n

r=0

n

r

d r

d

nr

dx r [u(x)] dx nr [v(x)],

n =

r

n! r!(n r)!

is the usual binomial coefficient.

Proof. This proceeds by induction on n, the result being trivial for n = 0 and reducing for n = 1 to the well-known rule for differentiating a product (once). Suppose then that

where u (r) = d r u

dx

r

d

n1

dx n1 [uv] =

n1

r=0

, v (n1r) =

d n1r v

dx

n1r

n 1

r

. Then

u (r) v (n1r)

for some n 1,

d

n

dx n (uv) =

n1

r=0

n 1

r

u (r) v (nr) + u (r+1) v (n1r)

where

= uv (n) +

n1

r=1

n 1

r

u (r) v (nr) +

n2

r=0

n 1

r

= uv (n) +

n1

r=1

n 1

r

u (r) v (nr) +

n1

r=1

n 1 r 1

u (r+1) v (n1r) + u (n) v

u (r) v (nr) + u (n) v

= uv (n) +

n1

r=1

n 1 + n 1

r 1

r

u (r) v (nr) + u (n) v,

n 1 + n 1

r 1

r

=

(n 1)! r!(n 1 r)! +

(n 1)! r)! = (r 1)!(n

(n 1)! r!(n

r)! [(n r) + r] = n ,

r

so

d

n

dx n (uv) = uv (n) +

n1

r=1

n

r

u (r) v (nr) + u (n) v =

n

r=0

This completes the proof by induction on n.

n

r

u (r) v (nr) .

1

r ) + u ( n ) v = n r =0 This completes the proof